Zinc(II)-induced control of the internalization of a near-infrared fluorescent probe by live cells - König, Sandra G.; Öz, Aliye Simin; Krämer, Roland (Molecular BioSystems, 2016)
We describe zinc-promoted cellular uptake of a near-infrared fluorophore modified with a terpyridine ligand. In response to varying concentrations of exogenous zinc(II), we observed increasing cellular uptake in live HeLa cells as well as other cell lines, whereas only negligible staining was detected in the absence of zinc(II).